“I delight in love, not in sacrifice”: Hosea 6:6 and Its Rereading in the Gospel of Matthew - Kubiś, Adam (Collectanea Theologica, 2021)
The first part of the article deals with four different understandings of Hosea 6:6 in the context of that entire book: (1) the repudiation of the cult as such; (2) the rejection of a particular notion of cult; (3) the priority of ethics over the cult; and (4) the symbiosis of cult and ethics, i.e. that an authentic cult interweaves ethical values and proper ritual conduct. The author concludes that the fourth interpretation best fits the message of the Book of Hosea. The second part of the article deals with the problem of the textual Vorlage which would have been used by Matthew. He seems to have quoted the Hebrew text in a way that remains faithful to his contemporary hermeneutical rule, according to which each element of a biblical parallelism was to be interpreted separately, based on the belief that every single line carried equal weight and conveyed a new truth or a new law. The Matthean rereading of Hosea 6:6, the focus of the third part, is presented from two perspectives: the synchronic and the diachronic. In the synchronic presentation, the main point of concern is the contribution of the quotes in 9:13 and 12:7 to the understanding of those Matthean pericopes. Finally, the diachronic reading deals with the Matthean use of Hosea 6:6 within the context of the Matthean community and its dialogue with the Rabbinic Judaism of that day.